Pengaruh Net Profit Margin, Return On Asset, dan Return On Equity Terhadap Harga Saham Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) - Ardiansyah Ardiansyah; Fitri Dede Wahyuni (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to determine NPM, ROA, and ROE on stock prices in companies listed on the Jakarta Islamic Index (JII). The population in this study are companies listed on the stock index on the IDX which consist of 30 companies in the 2020 JII period. With a sample of 30 companies using a saturated sample collection technique. The analytical method in this study uses multiple linear regression analysis. Based on the results of multiple linear regression, the regression equation is Y = 496.280 – 349.449X1+1.959X2+106.494X3. The correlation coefficient shows an R value of 0.229, so it can be concluded that the level of relationship between variables X1, X2 and X3 to variable Y has a low relationship. The dermination coefficient shows an R squared value of 0.053, this means that the effect of X1, X2 and X3 simultaneously on variable Y is 5.3% and is influenced by other variables outside the study of 94.7%. The results of the f test show that the significance value for the variables X1, X2 and X3 simultaneously on the Y variable is 0.698 > 0.05 and the calculated f value is 0.481 <f table 2.960, so it can be concluded that Ha is rejected then simultaneously the variables X1, X2 and X3 does not affect the Y variable. The results of the t test show that the sig value is 0.073 > 0.05, so it can be concluded that the residual values are normally distributed.